LLIN Evaluation in Uganda Project (LLINEUP): factors associated with childhood parasitaemia and anaemia 3 years after a national long-lasting insecticidal net distribution campaign: a cross-sectional survey - Sheila Rugnao; Samuel Gonahasa; Catherine Maiteki-Sebuguzi; Jimmy Opigo; Adoke Yeka; Agaba Katureebe; Mary Kyohere; Amy Lynd; Janet Hemingway; Martin J. Donnelly; Grant Dorsey; Moses R. Kamya; et al. (Malaria Journal, 2019)
Abstract Background Recent reductions in malaria burden have been attributed largely to long-lasting insecticidal nets (LLINs). In March–June 2017, approximately 3 years after a national LLIN distribution campaign, a cross-sectional community survey was conducted to investigate factors associated with malaria parasitaemia and anaemia, in advance of Uganda’s 2017–2018 LLIN campaign. Methods Households from 104 clusters in 48 districts were randomly selected using two-staged cluster sampling; 50 households were enrolled per cluster. Eligible children aged 2–10 years had blood obtained for a thick blood smear and those aged 2–4 years had haemoglobin measured. Associations between outcomes and variables of interest were assessed using log-binomial regression with generalized estimating equations to adjust for household clustering. Results In total, 5196 households, 8834 children with blood smear results, and 3753 with haemoglobin results were included. Only 16% of children lived in households with adequate LLIN coverage. Overall, parasite prevalence was 26.0%, ranging from 8.0% in the South West to 53.1% in East Central. Limiting data to children 2–4 years of age, parasite prevalence was 21.4%, up from 16.9% in 2014–2015 following the national LLIN campaign. In a multivariate analysis, factors associated with parasitaemia included region (East-Central vs South-Western; adjusted prevalence ratio [aPR] 6.45, 95% CI 5.55–7.50; p < 0.001), older age (8–10 vs 2–3 years; aPR 1.57, 95% CI 1.43–1.72; p < 0.001), living in a poorer household (poorest vs least poor tercile; aPR 2.32, 95% CI 2.05–2.63; p < 0.001), one constructed of traditional materials (aPR 1.13, 95% CI 1.03–1.24; p = 0.008), or without adequate LLIN coverage (aPR 1.30, 95% CI 1.14–1.48; p < 0.001). Overall, the prevalence of anaemia (haemoglobin < 10 g/dL) was 15.1% and varied geographically. In a multivariate analysis, factors associated with anaemia included region, younger age, living in a traditional house, and parasitaemia, which was the strongest predictor (aPR 2.50, 95% CI 2.12–2.95; p < 0.001). Conclusions Three years after a national LLIN campaign, LLIN coverage was low and parasite prevalence had increased. Parasite prevalence varied widely across Uganda; older children, those living in poorer households, and those with inadequate LLIN coverage, were at highest risk of parasitaemia. LLINs may need to be distributed more frequently through mass campaigns or continuously through sustainable mechanisms. Targeting interventions to geographic areas and populations at highest risk should also be considered.